(untitled) (Muitas Vozes, 2021)
Based on Functional Discourse Grammar model (Hengeveld; Mackenzie, 2008), this paper analyzes word order as a formal device for marking pragmatic distinctions. The aim is to investigate emphasis expression in Portuguese by means of word order. To do so, two objects of study are approached here: (i) the ordering of the interrogative constituent within Wh-Interrogatives; and (ii) the ordering of the item ainda (‘still’/‘yet’/‘even’) in comparative constructions. In relation to (i), this article reveals that the final order of the interrogative constituent in the sentence corresponds to an emphasis marking mechanism, in order to gain the addressee’s attention to the questioned content. In relation to (ii), the positions of ainda are associated with the expression of two different types of emphasis: emphasis and degree emphasis.